Performance of Pier-To-Pier Cap Connections of Integral Bridges Under Thermal and Seismic Loads - Saavedra-Flores, E; Avudaiappan-, S (Hindawi Limited, 2021)
In general, most highway bridges are constructed using prestressed concrete or steel girders. Mechanical joints are provided at the end of each span, to allow for the expansion of the bridge deck due to shrinkage of concrete, thermal effects, and deflections, among others. Smooth riding ability, low noise, wear resistance, and water tightness should be provided by expansion joints. In recent times, the increased traffic volume, along with heavier vehicle movements, adversely affects the performance of expansion joints in the bridge girder, causing a possible failure in one of the above-mentioned mechanisms. The deterioration of the expansion joint may result in leakage of water, concrete cracking, and potential problems in the underlying substructure. In this paper, we study the pier-pier cap connections in integral bridges subjected to thermal and seismic loads using analytical methods and experimental tests. © 2021 Siva Avudaiappan et al.